Antimicrobial activity of endemic Digitalis lamarckii Ivan from Turkey. - Benli, Mehlika; Yigit, Nazife; Geven, Fatmague; Guney, Kerim; Bingol, Umit (Natl Inst Science Communication-Niscair, 2009)
Antimicrobial activity of the methanolic extracts of leaves and flowers of D. lamarckii Ivan, (Scophulariaceae), an endemic plant species of Turkey, was tested on ten bacterial and four yeast strains. Effective antibacterial activity was observed in four bacterial strains. Minimum inhibitory concentration (MIC) was calculated by use of liquid culture tests and in all the four effective bacterial strains, the MIC was found to be >= 199.5 mg/ml. The minimum bactericidal concentration (MBC) of B. subtilis, S. aureus, and L. monocytogenes was calculated to be >= 199.5 mg/ml, and MBC value for Shigella was calculated as >= 399 mg/ml.

This study was financially supported by a grand from the Technical and Research Council of Turkey (TUBITAK, TBAG-HD/107(105T542)).

Technical and Research Council of TurkeyTurkiye Bilimsel ve Teknolojik Arastirma Kurumu (TUBITAK) [TUBITAK, TBAG-HD/107(105T542)]
Keywords: Antibacterial; Digitalis lamarckii; Antifungal Agents; Digitalis; Turkey; Plant Extracts; Methanol; Antimicrobial; Microbial Sensitivity Tests; Anti-Bacterial Agents